(untitled) (Engrami, 2025)
The new book, „Vedrina psihijatrije i njeni otmičari“ (eng. The Serenity of Psychiatry and Its Kidnappers), authored by Dr. Saša Branković, represents a valuable and authentic contribution to contemporary discussions on psychiatry and mental health. The author analyzes the loss of psychiatry’s optimistic narrative and humanistic essence—the transformation of a highly sophisticated, creative discipline once attentive to patients’ individual specificities into an impersonal, reductionist system that frustrates both those who are treated and those who provide treatment. Nevertheless, Branković simultaneously offers hope and guidance for restoring psychiatry as an authentic discipline devoted to the human being, reminding us that the essence of medicine must not be reduced to mere technical procedures but should remain oriented toward preserving dignity, health, and humanity. The work carries a strong humanistic message, emphasizing that integrity, knowledge, and courage are the foundations of genuine medical practice.